Antitumor and antimycobacterial activities of cyclopalladated complexes: X-ray structure of [Pd(C-2,N-dmba)(Br)(tu)] (dmba = N,N-dimethylbenzylamine, tu = thiourea) - Moro, Antonio C. [UNESP]; Mauro, Antonio Eduardo [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Ananias, Sandra R. [UNESP]; Quilles, Marcela B. [UNESP]; Carlos, Iracilda Z. [UNESP]; Pavan, Fernando R. [UNESP]; Leite, Clarice Q. F. [UNESP]; Hoerner, Manfredo (Elsevier France-editions Scientifiques Medicales Elsevier, 2009)
The reactions between [Pd(C-2,N-dmba)(mu-X)](2) (dmba = N,N-dimethylbenzylamine: X = Cl, Br) and thiourea (tu) in the 1:2 molar ratio at room temperature resulted in the mononuclear compounds [Pd(C-2,N-dmba)(Cl)(tu)] (1) and [Pd(C-2,N-dmba)(Br)(tu)] (2), which were characterized by elemental analyses and infrared (IR), H-1- and C-13{H-1} NMR spectroscopies. The crystal and molecular structures of 2 were determined by single-crystal X-ray diffraction. In vitro cytotoxicity assays of the compounds 1, 2, tu, dmba and cisplatin were carried out using two murine tumor cell lines, namely mammary adenocarcinoma (LM3) and lung adenocarcinoma (LP07). The compounds 1, 2, tu and dmba were also tested against Mycobacterium tuberculosis and their MIC values were determined. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: Cyclopalladated complex; Crystal structure; cytotoxicity assays; Mycobacterium tuberculosis; Antitumor; Thiourea